Atrial Fibrillation in Primary Aldosteronism - Pan, Chien-Ting; Tsai, Cheng-Hsuan; Chen, Zheng-Wei; Chang, Yi-Yao; Wu, Vin-Cent; Hung, Chi-Sheng; Lin, Yen-Hung; the TAIPAI Study Group (Hormone and Metabolic Research, 2020)
Primary aldosteronism (PA) is the most common cause of secondary hypertension. Increasing evidence has demonstrated an increased cardiovascular risk in patients with PA compared to those with essential hypertension (EH), including atrial fibrillation (AF), the most prevalent arrhythmia among adults that is associated with an elevated risk of subsequent cerebro-cardiovascular adverse events. The mechanisms of increased prevalence of AF in PA patients are complex. Excessive aldosterone production is regarded to be a key component in the pathogenesis of AF, in addition to arterial hypertension and electrolyte imbalance. In addition, several translational and clinical studies have reported that structural remodeling with atrial fibrosis and electrical remodeling with arrhythmogenicity induced by an excess of aldosterone also play major roles in AF genesis. Clinical studies from several registries and meta-analysis have reported an increased prevalence and risk of AF in PA patients compared to EH patients. Recent trials have further demonstrated a reduction in the risk of new-onset atrial fibrillation (NOAF) after adrenalectomy, while the results of medical treatment with mineralocorticoid receptor antagonists (MRAs) have been inconsistent. This review outlines the current evidence of the relationship between PA and AF, and highlights recent progress in the management of PA with regards to the development of AF.
Keywords: atrial fibrillation; primary aldosteronism; aldosterone; atrial remodeling